INOVASI PERANCANGAN MOTIF TIE-DYE (IKAT CELUP) DI KOTA YOGYAKARTA - Sugeng Wardoyo; Suryo Tri Widodo (Institut Seni Indonesia Yogyakarta, 2016)
The existence of tie-dye in Yogyakarta city as a craft products has promised prospect.Uniqueness of tie-dye compare with another crafts textiles is in processes making which is simpleto result a motifs on to the fabric are faster and easier to learn about. As a tourism city,Yogyakarta has potential to develop tie-dye also as a good place to produce and market tie-dyeproducts. So inovation in designing new tie-dye motifs become positive step, because demandtie-dye products in market rapidly, beside always on dynamic market.Keywords: Craft textiles, Textile motifs, Tie-dye, Jumputan Yogyakarta